O princípio de Cavalieri e o volume da esfera - Greyce Contini Pilati (2015)
In this work, we estimate the volume of the sphere by using approximations of Riemann sums using cylinders, prisms of square and rectangular base and the inscribed of geometric solids in sphere of radius r. We showed the existence of a prism with square base whose volume is equal to the volume of the sphere, using the quadrature the circle. In addition demonstrate the principle of Cavalieri for areas and volumes and we calculate the volume of the sphere as is discussed in the textbooks, which use this principle as a resource